The Impact And Translatability Of Sound Segment And Signs In Poetry: An Intercultural Study - Jafari, Sepideh Moghaddas (2019)
Poetry has always been proximately associated with music. It is indeed the art of rhythm and sounds. It, just as being something that we see, is additionally something that we hear. Amid translation problems, poetry translation is thought to be the most difficult zone puzzling translators and experts inside the disciplines of translation studies, literature, and linguistics as well. Translation of poetry as a hitherto unanalyzed ‘black box’ (Francis 2006) has been the most disputed and argued subject since times past. According to scholars and translators, poetry is perhaps the most complicated text among literary texts and genres to translate, if not impossible, due to its aesthetic signs and features, images, musical aspects, as well as cultural issues. Accordingly, the general aim of this study is to investigate the impact, effect, and translatability of sound segment and signs in poetry. It also tries to investigate the impact of these aesthetic elements in the poetry of (two) different cultures (of West and East in general and English and Persian in particular). The objectives of the study are reached through an eclectic combination of theories. The corpora of this study comprise ten poems from the most famous poets of West and East i.e. Shakespeare and Hafiz. It is concluded that the sound segment and signs as the repeated sounds which make the music of poetry are often very momentous and significant in terms of imagery and construction of meaning in poetry. The results also show no difference between Western poetry and Non-Western (Eastern) in terms of imagery and creation of senses via sound segment and signs.